Prognostic value of postinduction medullary myeloid recovery by flow cytometry in acute myeloid leukemia - Row, Céline; Lechevalier, Nicolas; Vial, Jean Philippe; Mimoun, Aguirre; Bastie, Jean Noel; Lafon, Ingrid; Pigneux, Arnaud; Leguay, Thibaut; Callanan, Mary; Maynadie, Marc; Béné, Marie C.; Dumas, Pierre Yves; et al. (EJHaem, 2024)
Risk stratification and treatment response evaluation are key features in acute myeloid leukemia (AML) management. Immunophenotypic and molecular approaches all rely on the detection of persisting leukemic cells by measurable residual disease techniques. A new approach is proposed here by assessing medullary myeloid maturation by flow cytometry through a myeloid progenitor ratio (MPR). The normal MPR range was defined using reference normal bone marrows (n = 48). MPR was considered balanced if between 1 and 4 and unbalanced if < 1 or > 4. MPR was retrospectively assessed at baseline and post‐induction for 206 newly diagnosed AML patients eligible for intensive treatment from two different French centers. All AML baseline MPR were unbalanced and thus significantly different from normal MPR (p < 0.0001). Patients with an unbalanced MPR after induction had worse 3‐year overall survival (OS) (44.4% vs. 80.2%, HR, 2.96; 95% CI, 1.81–4.84, p < 0.0001) and 3‐year relapse free survival (RFS) (38.7% vs. 64.4%, HR, 2.11; 95% CI, 1.39–3.18, p < 0.001). In multivariate analysis, postinduction unbalanced MPR was significantly associated with shorter OS and RFS regardless of the European LeukemiaNet 2010 risk stratification or NPM1/FLT3‐ITD status. A balanced postinduction MPR conversely conferred favorable outcomes and reflects medullary myeloid recovery. Unbalanced post‐induction myeloid progenitor ratio (MPR) assessed by flow cytometry is a strong predictor of poorer survival in AML patients.